A concept for a 3D-printed patient-specific stereotaxy platform for brain biopsy -a canine cadaver study-. (June 2019) - Müller, Marcel; Winkler, Dirk; Möbius, Robert; Sauerstein, Tobias; Scholz, Sebastian; Gutmann, Sarah; Flegel, Thomas; Meixensberger, Jürgen; Drossel, Welf-Guntram; Grunert, Ronny
Abstract: The treatment of intracranial lesions requires a precise diagnosis with subsequent identification of an adequate therapeutic approach. Stereotactic tumor biopsy may be considered the safest neurosurgical procedure in terms of anticipated results and potential surgical complications. The aim of the present paper was to demonstrate a new method of stereotactic biopsy, based on a patient-specific 3D printed platform in dogs. The system was tested on two canine cadavers, a small (Shih Tzu) and a large (Labrador) breed. Imaginary biopsy targets were defined in a superficial (caudate nucleus) and a deep (piriform lobe) position. Based on 3 Tesla MRI, individualized stereotactic platforms were designed using a semi-automatic approach, and manufactured additively using ABS M30. A pre- and intra-operative CT was performed to compare the planned vs. the realized needle position for precision analyses of the procedure. The target points varied with a precision between 0.09 mm and 0.48 mm. Manufacturing time required 480 to 700 min per platform. The presented patient-specific stereotactic system seems a suitable instrument for application in small animal neurosurgery. In particular, the implementation of relevant stereotactic data may help performing the procedure in rapid sequence and with higher precision than currently-used systems. Required adjustments and adaptions to the respective anatomical conditions are omitted and make the procedure reliable and safe. Highlights: Stereotactic tumor biopsy is the safest neurosurgical procedure for diagnose in intracranial lesions. Patient-specific stereotactic system based on 3D print seems to be more precise and effective than currently used systems. Patient-specific stereotactic system is a suitable instrument for use in the field of small animal neurosurgery.